Experimental investigation on spark ignition engine using blends of bio-ethanol produced from citrus peel wastes. Issue 2 (17th February 2017) - Karthikeyan, A.; Venkatesh, D.; Ramkumar, T.
Abstract : The performance and pollutant emissions of a four stroke spark ignition engine operating on gasoline and bio-ethanol blends were investigated experimentally. The citrus peel wastes were grinded and subjected to simple distillation to removed -limonene and then the remains were kept in an autoclave at a temperature of 120°C for 15 min. Finally, by doing simple distillation, bio-ethanol was extracted. From the experiments, the specific fuel consumption (SFC) was slightly increased and the brake thermal efficiency was slightly decreased. Exhaust gas emissions were measured and analysed for hydrocarbons (HC), carbon dioxide (CO2 ), carbon monoxide (CO) and oxides of nitrogen (NO x ) at an engine speed of 2500 rpm. The concentration of CO and HC emissions in the exhaust pipe was found to be decreased when bio-ethanol blends were used. The concentration of CO2 was found to be slightly increased and NO x was reduced when ethanol blends were used.